Development and validation of Kongoh ver. 3.0.1: Open-source software for DNA mixture interpretation in the GlobalFiler system based on a quantitative continuous model. (February 2022) - Manabe, Sho; Fukagawa, Takashi; Fujii, Koji; Mizuno, Natsuko; Sekiguchi, Kazumasa; Akane, Atsushi; Tamaki, Keiji
Highlights: Kongoh is probabilistic genotyping software based on a continuous model. Kongoh was updated to interpret DNA profiles typed by the GlobalFiler system. The new version of Kongoh considers forward, double-back, and minus 2-nt stutters. Kongoh was validated using 2–4-person mixtures and DNA profiles with degradation. Likelihood ratios calculated by Kongoh demonstrated the desired trend. Abstract: Probabilistic genotyping software based on continuous models is effective for interpreting DNA profiles derived from DNA mixtures and small DNA samples. In this study, we updated our previously developed Kongoh software (to ver. 3.0.1) to interpret DNA profiles typed using the GlobalFiler™ PCR Amplification Kit. Recently, highly sensitive typing systems such as the GlobalFiler system have facilitated the detection of forward, double-back, and minus 2-nt stutters; therefore, we implemented statistical models for these stutters in Kongoh . In addition, we validated the new version of Kongoh using 2–4-person mixtures and DNA profiles with degradation in the GlobalFiler system. The likelihood ratios (LRs) for true contributors and non-contributors were well separated as the information increased (i.e., larger peak height and fewer contributors), and these LRs tended to neutrality as the information decreased. These trends were observed even in profiles with DNA degradation. The LR values were highly reproducible, and the accuracy of the calculation was also confirmed. Therefore, Kongoh ver. 3.0.1 is useful for interpreting DNA mixtures and degraded DNA samples in the GlobalFiler system.